Lane Line Detection for Autonomous Vehicles using Computer Vision (International Journal of Food and Nutritional Sciences, 2022)
Lane line detection is a crucial component of modernized driver assistance technologies and it enhances the overall safeness of the vehicle when it is moving. Real time vision-based system that detects lane lines for autonomous vehicles using a front-facing camera on a vehicle, is introduced. By leveraging computer vision-based technologies, the suggested system can identify lane boundaries. Utilizing a live video stream, we were able to identify lane borders, curve radii, and lane orientation. Utilizing this information, the system can manage the steering wheel automatically to perform smooth bends on highways without the need for user input, improving safety and comfort while ensuring that the car stays centered within the lane lines. The camera used to film this video was perched above the car. After importing this video, we fixed the distortion introduced by the camera. To extract the road markings from the raw picture, color and gradient threshold strategies are applied to the unobstructed picture. A